Atypical depression and alcohol misuse are related to the cardiovascular risk in the general population. (7th December 2012) - Glaus, J.; Vandeleur, C.; Gholam‐Rezaee, M.; Castelao, E.; Perrin, M.; Rothen, S.; Bovet, P.; Marques‐Vidal, P.; von, R.; Merikangas, K.; Mooser, V.; Waterworth, D. M.; et al.
<x xml:space="preserve">Abstract</x> Objective The aims of the present study were to assess the associations between mood, anxiety and substance use disorders, including their subtypes, and the prevalence of cardiovascular risk factors (CVRFs). Method Thorough physical investigations, biological measures and standardized interview techniques were used to assess 3716 subjects of an urban area, aged 35–66 years. Results Atypical depression was associated with increased prevalence of overweight, diabetes and the metabolic syndrome (OR = 1.5, 95% C.I. 1.1–2.0; OR = 2.0, 95% C.I. 1.1–3.5, OR = 1.6, 95% C.I. 1.0–2.4 respectively), whereas decreased prevalence of overweight was found in melancholic (OR = 0.7, 95% C.I. 0.6–0.9) and unspecified depression (OR = 0.8, 95% C.I. 0.7–1.0). Alcohol abuse was associated with diabetes (OR = 1.8, 95% C.I. 1.1–2.9) and dyslipidemia (OR = 1.3, 95% C.I. 1.0–1.8), alcohol dependence with dyslipidemia only (OR = 1.4, 95% C.I. 1.0–2.0). Almost all mental disorders were associated with a lifetime history of regular cigarette smoking, and atypical depression, alcohol misuse and drug dependence were associated with inactivity. Conclusion To conclude results emphasize the need to subtype depression and to pay particular attention to the atypical subtype. Comorbid alcohol misuse may further increase the cardiovascular risk. Efforts to diminish smoking in subjects with mental disorders could be crucial measures to reduce their high incidence of cardiovascular disease.